Managing the risks of big-data environment through data protection law: the position in Malaysia and Indonesia - Zulhuda, Sonny; Abdul Ghani Azmi, Ida Madieha; Hakiem, Nashrul (2015)
The legal risks of “Big Data” are real and potentially damaging. The proliferation of data from ubiquitous sources accumulated with increasing economic values attached to those data is often not balanced with adequate awareness and a prudent risk management. The fact that the end-users are not equally vigilant makes it easier for criminal minds to profit illegitimately from the IT services. This presentation undertakes two major tasks. Firstly, examining the types of legal risks involved in the provision of cyber and IT-related services which occur in a Big Data environment. Secondly, it highlights some aspects of data privacy and security laws based on the Malaysian and Indonesian legal framework.